Impedance-Based Miniaturized Biosensor for Ultrasensitive and Fast Prostate-Specific Antigen Detection. (17th February 2011) - Chornokur, Ganna; Arya, Sunil K.; Phelan, Catherine; Tanner, Richard; Bhansali, Shekhar
Abstract : This paper reports the successful fabrication of an impedance-based miniaturized biosensor and its application for ultrasensitive Prostate-Specific Antigen (PSA) detection in standard and real human plasma solution, spiked with different PSA concentrations. The sensor was fabricated using photolithographic techniques, while monoclonal antibodies specific to human PSA were used as primary capture antibodies. Electrochemical impedance spectroscopy (EIS) was employed as a detection technique. The sensor exhibited a detection limit of 1 pg/ml for PSA with minimal nonspecific binding (NSB). This detection limit is an order of magnitude lower than commercial PSA ELISA assays available on the market. The sensor can be easily modified into an array for the detection of other biomolecules of interest, enabling accurate, ultrasensitive, and inexpensive point-of-care sensing technologies.